2021
DOI: 10.1038/s41467-021-25912-w
|View full text |Cite
|
Sign up to set email alerts
|

Quantum anomalous Hall edge channels survive up to the Curie temperature

Abstract: Achieving metrological precision of quantum anomalous Hall resistance quantization at zero magnetic field so far remains limited to temperatures of the order of 20 mK, while the Curie temperature in the involved material is as high as 20 K. The reason for this discrepancy remains one of the biggest open questions surrounding the effect, and is the focus of this article. Here we show, through a careful analysis of the non-local voltages on a multi-terminal Corbino geometry, that the chiral edge channels continu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…A detailed transport study provides strong evidences to show that the nonequilibrium current flows primarily through the two-dimensional bulk of the QAH insulator rather than, as had been previously assumed, through the edges [19]. Consistently, it further shows that the transport in the QAH insulator of the Corbino geometry in a previous study [20] can be described by the solution to Laplace equation, which demonstrates a spatially-uniform conductivity (i.e. the current propagates uniformly through the entire system) rather than the bulk-boundary correspondence.…”
Section: Introductionsupporting
confidence: 81%
“…A detailed transport study provides strong evidences to show that the nonequilibrium current flows primarily through the two-dimensional bulk of the QAH insulator rather than, as had been previously assumed, through the edges [19]. Consistently, it further shows that the transport in the QAH insulator of the Corbino geometry in a previous study [20] can be described by the solution to Laplace equation, which demonstrates a spatially-uniform conductivity (i.e. the current propagates uniformly through the entire system) rather than the bulk-boundary correspondence.…”
Section: Introductionsupporting
confidence: 81%
“…It was also found that thermally activated bulk conductance was mostly responsible for quantization breakdown. 429 These results show promise on the availability of topological protection from MTI edge channels for developing a resistance standard.…”
Section: Quantum Anomalous Hall Effect Inmentioning
confidence: 87%
“…One of the last remaining limitations to be lifted are the stringent temperature requirements, which are currently in the 10 to 100 mK range. Fijalkowski et al 429 show that the chiral edge channels associated with the QAHE continue to exist without applied magnetic field up to the Curie temperature (about 20 K) of bulk ferromagnetism in their TI system. This conclusion was reached through a careful analysis of nonlocal voltages in Corbino-type devices.…”
Section: Quantum Anomalous Hall Effect Inmentioning
confidence: 99%
“…Note added: After submission, we became aware of the work by Fijalkowski et al reporting nonlocal transport measurements on V-doped (Bi x Sb 1−x ) 2 Te 3 in multiterminal Corbino devices [41].…”
Section: Discussionmentioning
confidence: 99%